2014
DOI: 10.1002/smll.201402144
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Height of Ultrathin PbS Nanosheets and Their Application as Field-Effect Transistors

Abstract: Two-dimensional, solution-processable semiconductor materials are anticipated to be used in low-cost electronic applications, such as transistors and solar cells. Here, lead sulfide nanosheets with a lateral size of several micrometers are synthesized and it is shown how their height can be tuned by the variation of the ligand concentrations. As a consequence of the adjustability of the nanosheets' height between 4 to more than 20 nm charge carriers are in confinement, which has a decisive impact on their elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 46 publications
3
92
1
Order By: Relevance
“…8,9,10,11,18,19 Here, we demonstrated that amines and aliphatic fluorides are also suitable for the growth of twodimensional lead sulfide shapes at reaction temperatures of 170 °C. By omitting the coligand, the only ligand left in the solution is oleic acid.…”
Section: Oleic Acid As Sole Ligandmentioning
confidence: 82%
“…8,9,10,11,18,19 Here, we demonstrated that amines and aliphatic fluorides are also suitable for the growth of twodimensional lead sulfide shapes at reaction temperatures of 170 °C. By omitting the coligand, the only ligand left in the solution is oleic acid.…”
Section: Oleic Acid As Sole Ligandmentioning
confidence: 82%
“…We synthesized PbS nanosheets with lateral dimensions of up to 5 μm and tunable thickness of 2–20 nm by introducing different amounts of oleic acid to the synthesis192022 (for crystallographic characterization see Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The height of the nanosheets directly determines the band gap of the material by confinement23. This tunability is of advantage for the performance of applications such as transistors, photodetectors and solar cells17182023. The synthesis of the nanosheets is independent of the fabrication of the devices, which makes it practical for industrial applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the 2D aspect of the nanoparticles leads to a high exciton binding energy [7,8] (≈250 meV) and a fast photoluminescence lifetime. While the spectroscopic properties have attracted huge interest in particular for stimulated emission, the integration of NPL [9] into conductive devices remains far less investigated [10,11]. Nevertheless, NPL look promising because their sharp optical features can be used to develop narrow emission electroluminescence devices [12] or photodetectors with finely controlled cut-off wavelengths.…”
Section: Introductionmentioning
confidence: 98%